Association Between Nuclear Lamin A/C R482Q Mutation and Partial Lipodystrophy with Hyperinsulinemia, Dyslipidemia, Hypertension, and Diabetes - Hegele, Robert A.; Anderson, Carol M.; Wang, Jian; Jones, Doreen C.; Cao, Henian (Genome Research, 2000)
Nuclear lamins A and C are encoded by LMNA and are present in terminally differentiated cells. Lamins participate in DNA replication, chromatin organization, arrangement of nuclear pores, nuclear growth, and anchorage of nuclear membranes. In several Canadian probands with partial lipodystrophy, since found to have a common ancestor, we identified a rare novel LMNA mutation, R482Q, that completely cosegregated with the partial lipodystrophy phenotype. We evaluated the relationship between quantitative metabolic phenotypes in both diabetic and nondiabetic carriers of LMNA R482Q and family controls, who were LMNA R482/R482 homozygotes. We found that when compared with LMNA R482/R482 homozygotes: (1) diabetic LMNA Q482/R482 heterozygotes had significantly higher glucose, glycosylated hemoglobin, triglycerides, insulin and C-peptide, and significantly lower HDL cholesterol; and (2) nondiabeticLMNA Q482/R482 heterozygotes had significantly higher triglycerides, insulin and C-peptide, and significantly lower HDL cholesterol. We also found that diabetic LMNA Q482/R482 heterozygotes were older and more likely to take antihypertensive medications. Thus, LMNA R482Q was associated with lipodystrophy, hyperinsulinemia, dyslipidemia, diabetes, and hypertension. The results indicate that perturbations in plasma lipids precede the plasma glucose abnormalities in LMNAQ482-associated hyperinsulinemia. Thus, rare mutations in a nuclear structural protein can be associated with markedly abnormal qualitative and quantitative metabolic phenotypes
10.1101/gr.10.5.652